Legal Certainty of Land Ownership Rights By Foreign Nationals Through Nominee Agreements - Mita Kirani, Salsa; Lanontji, Muryanto; Wahyudi Umar (Universitas Muhammadiyah Surakarta, 2024)
The purpose of this study to examine the legal certainty related to the ownership of land rights by foreign nationals (WNA) through name loan agreements or nominees in Indonesia. The methodology used is normative legal research with a legislative and conceptual approach, as well as analysis of primary and secondary legal materials. The results of the study show that the practice of nominee agreements is often considered illegal and has the potential to cause legal disputes, because it is contrary to Law No. 5 of 1960 concerning Agrarian Principles which only allows Indonesian citizens to have property rights to land. In addition, this agreement can result in losses for all parties involved, including foreign citizens (WNA) who lose their rights and Indonesian citizens (WNI) who lend their names. This research provides an understanding of the need for clearer regulations to protect the interests of all parties and prevent the abuse of the law in land tenure by foreign nationals (WNA) in Indonesia.